Effect of pre-storage treatment with bio-pesticides for the control of seed borne fungi in rice - and JANKI KANDHARI, PRASHANT P. JAMBHULKAR (Indian Phytopathology, 2007)
Rice is subjected to considerable number of stresses during storage. Out of ten rice cultivars, four were selected on the basis of physical purity, high germination and minimum mycoflora. The seeds of these four cultivars namely Pusa 44, PRH 10, Jaya and Pusa Sugandh 2 were treated with three plant extracts (Piper bet/e, Allium sativum, Calotropis procera) at 0.5% and 1% concentrations, one phytochemical (geraniol), two antagonists (Kalisena SO, Trichoderma harzianum) and two fungicides (vitavax 200 and carbendazim SOWP).Seed germination, seedling vigour and seed health of above said cultivars were observed at an interval of 60 days. Seed treatment with leaf extract of Piper betle (0.5%) increased seed germination and seedling vigour and decreased mycoflora even after six months of storage. P. bet/e 0.5% extract was found as a potent biopesticide against most of the storage and field fungi associated with rice seeds . Extract from the stem of Calotropis procera (1%) and Geraniol (1%) had phytotoxic property however lower concentration (0.5%) showed positive response.